T-Cells Proliferation and Serum Cytokine levels in Type 1 Diabetic Children - Saleh, Eman Mahdi (AL-Kindy College Medical Journal, 2011)
Background: There is plenty of evidence suggesting that involvement of several groups of viruses in the development and / or acceleration of Type 1 Diabetes Mellitus (T1DM). Objective: To analyze the T- cell proliferation in the presence of Coxsackie virus B5 (CVB5), Polio and Adenovirus antigens in addition to assessment of Interferon- gamma (IFN-γ), Interleukins (IL-10 and IL-6). Methods: In 60 Iraqi T1DM children with recent onset of T1DM, Lymphocyte proliferation was analyzed using Methylthiazol tetrazolium (MTT) assay by culturing Peripheral Blood Lymphocytes (PBLs) with Coxsackie Virus B5 (CVB5), Adenovirus, and Polio vaccine. Serum Interferon-γ, IL-10 and IL-6 were quantified by sandwich ELISA. Results: No significant differences were shown in the PBL proliferative percentage in response to Con-A mitogen and tested viruses (CVB5 and Adenovirus) between T1DM and healthy controls, but it showed a significant decline in patients in response to Polio vaccine. Higher significant serum levels of IFN-γ, IL-10, and Il-6 were observed in the investigated patients compared to controls (p<0.05). Mean PBL proliferative percentage in response to tested viral antigens was correlated with the serum IFN-γ, IL-6 and IL-10 levels. Conclusions: In children with new- onset diabetes, mean proliferative percentage of Peripheral Blood Lymphocytes was generally decreased. A significant elevation of serum levels of IFN-γ, IL-10 and IL-6 were observed, which is significantly correlated to mean proliferative responses of PBL to viral antigens.